UJI KINERJA DAN ANALISIS EKONOMI RICE MILLING UNIT SINGEL PHASE DI DESA LONG LESS - Joko Krisbiyantoro; Dhani Aryanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The rice milling business that was most widely used by the community in the Busang sub-district was the Rice Milling Unit single phase. This study aims to test the performance and economic analysis of a single-phase rice milling business. The research method was descriptive using secondary data from the rice milling business and primary data obtained from interviews. The data parameters in this study were: work capacity, yield, efficiency, grain quality, stripping quality, and economic analysis. The rice varieties used in the performance test were kawan and sumping rice varieties. The results of the performance test of the single-phase rice mill is that the average working capacity of the kawan rice variety was 260.9 kg/hour with a yield of 65% and the sumping rice variety was 254.2 kg/hour with a yield of 59%. The stripping efficiency value of the kawan rice variety was 39.27% while the sumping rice variety was 34.78%. Milled rice was not yet the criteria for medium rice (SNI 01-0224-1987), this was due to the milling process that is carried out repeatedly so that it produces rice groats were high. The economic analysis of the rice milling business in Long Lees Village has an NPV value of Rp. 42,536,000, a B/C ratio value of 1.67, and an IRR value of 37% which indicates that the rice milling business was feasible.